1995
DOI: 10.1002/pssb.2221910114
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling through Ultrasmall NIS Junctions in Terms of Andreev Reflection. A Nonlinear Response Approach

Abstract: The Andreev current through an ultrasmall NIS junction is calculated in a systematic way by means of a nonlinear response approach basing on the elementary Hamiltonian of quasiparticle tunneling. The voltage dependence of current and differential conductance as well as the Andreev conductance are derived for low-and high-impedance environments, respectively. 73. 40, 74.50

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…To determine which is responsible, and to confirm the cause of the flat region, we examine theoretically the rates for all processes. Using existing formulas from earlier work on normal metal insulator superconductor (NIS) junctions, we calculate rates for quasiparticle tunneling [30] and Andreev reflection [31,32] from each of the leads. The former follow from Fermi's golden rule, while the latter are derived using a nonlinear response approach.…”
mentioning
confidence: 99%
“…To determine which is responsible, and to confirm the cause of the flat region, we examine theoretically the rates for all processes. Using existing formulas from earlier work on normal metal insulator superconductor (NIS) junctions, we calculate rates for quasiparticle tunneling [30] and Andreev reflection [31,32] from each of the leads. The former follow from Fermi's golden rule, while the latter are derived using a nonlinear response approach.…”
mentioning
confidence: 99%
“…The important feature of this novel Andreev process is that it appears in lowest (first) order approximation with respect to the tunneling barrier transparencythe same order as the usual tunneling current exhibiting the pseudogap. This effect is stronger than the standard Andreev conductance of a N-I-S junction which is proportional to the square of the transparency 11,12 . The reason is that the fluctuation-induced domain of superconducting phase in the biased electrode is not separated from the surrounding normal phase by any barrier and thus the process of Andreev-like reflection does not involve an additional tunneling process.…”
mentioning
confidence: 82%
“…(11), which makes the effect strongly temperature dependent close to the transition point. The discovered LBA, appearing already in the first order of the transparency, qualitatively differs from the well-known Andreev conductance of a superconducting micro-constriction [19], occurring below the transition temperature, which rapidly disappears when the latter departs from the metallic towards the tunneling regime (in the classical paper [19] this decrease is governed by an additional factor Z 2 (Z is a dimensionless interfacial scattering strength) to transparency, which vanishes for an insulating barrier, while the authors of [20] explicitly demonstrated that the Andreev conductance of a N-I-S junction is directly proportional to the square of its transparency). The reason for this discrepancy is that the fluctuation-induced superconducting regions in the biased electrode are not separated by any barrier from the surrounding normal phase and thus the process of Andreev reflection does not involve an additional tunneling process.…”
Section: (C))mentioning
confidence: 92%